Using nonlinear dynamics analysis to evaluate time response of cupping therapy with different intervention timings on reducing muscle fatigue - Jia, Yuanyuan; Liu, Yining; Lei, Juntian; Wang, Huihui; Wang, Rong; Zhao, Pengrui; Sun, Tingting; Hou, Xiao (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: The purpose of this study was to use the sEMG nonlinear analysis to assess the difference of time response of cupping therapy between different intervention timings after muscle fatigue. Methods: This randomized controlled trial recruited 26 healthy volunteers. Cupping therapy was applied before (i.e., pre-condition) or after (i.e., post-condition) muscle fatigue. The sEMG signals during the maximal voluntary isometric contractions (MVC) of the biceps were recorded at four time points (i.e., baseline; post 1: immediate after cupping-fatigue/fatigue-cupping interventions; post 2: 3 h after cupping-fatigue/fatigue-cupping interventions; post 3: 6 h after cupping-fatigue/fatigue-cupping interventions). Two nonlinear sEMG indexes (sample entropy, SampEn; and percent determinism based on recurrence quantification analysis, %DET) were used to evaluate the recovery from exercise-introduced muscle fatigue. Results: The SampEn and %DET change rate did not show any significant differences in the pre-condition group. However, there were significant delayed effects instead of immediate effects on improving muscle fatigue in the post-condition group (SampEn change rate: baseline 0.0000 ± 0.0000 vs. post 2 0.1105 ± 0.2253, P < 0.05; baseline 0.0000 ± 0.0000 vs. post 3 0.0627 ± 0.4665, P < 0.05; post 1 -0.0321 ± 0.2668 vs. post 3 0.0627 ± 0.4665, P < 0.05; and %DET change rate: baseline 0.0000 ± 0.0000 vs. post 2 -0.1240 ± 0.1357, P < 0.01; baseline 0.0000 ± 0.0000 vs. post 3 0.0704 ± 0.6495, P < 0.05; post 1 0.0700 ± 0.3819 vs. post 3 0.0704 ± 0.6495, P < 0.05). Moreover, the SampEn change rate of the post-condition group (0.1105 ± 0.2253) was significantly higher than that of the pre-condition group (0.0006 ± 0.0634, P < 0.05) at the post 2 time point. No more significant between-groups difference was found in this study. Conclusion: This is the first study demonstrating that both the pre-condition and post-condition of cupping therapy are useful for reducing muscle fatigue. The post-condition cupping therapy can effectively alleviate exercise-induced muscle fatigue and there is a significant delayed effect, especially 3 h after the interventions. Although the pre-condition cupping therapy can not significantly enhance muscle manifestations, it can recover muscles into a non-fatigued state.